2019
DOI: 10.3390/nano9030465
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles for Bioapplications: Study of the Cytotoxicity of Water Dispersible CdSe(S) and CdSe(S)/ZnO Quantum Dots

Abstract: Semiconductor nanocrystals or quantum dots (QDs) have unique optical and physical properties that make them potential imaging tools in biological and medical applications. However, concerns over the aqueous dispersivity, toxicity to cells, and stability in biological environments may limit the use of QDs in such applications. Here, we report an investigation into the cytotoxicity of aqueously dispersed CdSe(S) and CdSe(S)/ZnO core/shell QDs in the presence of human colorectal carcinoma cells (HCT-116) and a hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Although shell greatly reduces ion release, QDs can continue to release ions in the acidic environment of lysosomes, leading to severe oxidative stress and increased apoptosis rate (Brunetti et al, 2013). Moreover, as a recent report by Mirnajafizadeh et al, the preparation of ZnS shell will introduce a new toxic ion of acetate contributing to other portions of cytotoxicity (Mirnajafizadeh, Ramsey, McAlpine, Wang, & Stride, 2019). Therefore, preparation conditions greatly affect the release of ions and subsequently affect toxicity (Murase, Horie, Sawai, & Kawasaki, 2019).…”
Section: Cytotoxicity Of Qdsmentioning
confidence: 99%
“…Although shell greatly reduces ion release, QDs can continue to release ions in the acidic environment of lysosomes, leading to severe oxidative stress and increased apoptosis rate (Brunetti et al, 2013). Moreover, as a recent report by Mirnajafizadeh et al, the preparation of ZnS shell will introduce a new toxic ion of acetate contributing to other portions of cytotoxicity (Mirnajafizadeh, Ramsey, McAlpine, Wang, & Stride, 2019). Therefore, preparation conditions greatly affect the release of ions and subsequently affect toxicity (Murase, Horie, Sawai, & Kawasaki, 2019).…”
Section: Cytotoxicity Of Qdsmentioning
confidence: 99%
“…[14][15][16][17][18] In addition, the cytotoxicity of QDs can be reduced and targeting of tumor cells can be enhanced through modification of QD surfaces using biomolecules. [19][20][21][22][23] Therefore, when interfaced with biological molecules including proteins, peptides, carbohydrates or DNA, the resulting QD-biocomposites have widespread applicability in areas ranging from cellular fluorescence imaging to in vivo fluorescence imaging. [24][25][26][27][28][29][30] However, following surface modification of QDs, it is important to retain its fundamental properties, such as uniform dispersion and to ensure that functional groups remain available for biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor quantum dots (QDs)—including CdS [ 7 , 8 ], CdSe [ 9 , 10 ], CdTe [ 11 , 12 ], C 3 N 4 [ 13 ], ZnO [ 14 ] and ZnSe [ 15 ]—have been coupled with photocatalysts to form heterostructures with improved photoactivity. For instance, Sun et al reported a CdS QDs-sensitized TiO 2 photocatalyst with outstanding NO photo-oxidation performance [ 16 ].…”
Section: Introductionmentioning
confidence: 99%